Is chondroitin sulfate responsible for the biological effects attributed to the GC protein-derived Macrophage Activating Factor (GcMAF)?. (September 2016) - Ruggiero, Marco; Reinwald, Heinz; Pacini, Stefania
Abstract: We hypothesize that a plasma glycosaminoglycan, chondroitin sulfate, may be responsible for the biological and clinical effects attributed to the Gc protein-derived Macrophage Activating Factor (GcMAF), a protein that is extracted from human blood. Thus, Gc protein binds chondroitin sulfate on the cell surface and such an interaction may occur also in blood, colostrum and milk. This interpretation would solve the inconsistencies encountered in explaining the effects of GcMAF in vitro and in vivo . According to our model, the Gc protein or the GcMAF bind to chondroitin sulfate both on the cell surface and in bodily fluids, and the resulting multimolecular complexes, under the form of oligomers trigger a transmembrane signal or, alternatively, are internalized and convey the signal directly to the nucleus thus eliciting the diverse biological effects observed for both GcMAF and chondroitin sulfate.